Interface modifier, perovskite battery and method for preparing perovskite battery

By using 8-hydroxyquinoline aluminum as an interface modifier between the perovskite layer and the electron transport layer of the perovskite solar cell, the interface defect problem caused by the difficulty in regulating the growth direction of the perovskite solar cell is solved, and the photoelectric conversion efficiency and stability are significantly improved.

CN119789664APending Publication Date: 2025-04-08旗滨新能源发展(深圳)有限责任公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411991786.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

During the annealing process, the growth direction of the perovskite crystals is difficult to regulate, resulting in a large number of defects in the interface between the perovskite layer and the electron transport layer, trapping charge carriers, resulting in a significant reduction in photoelectric conversion efficiency and stability.

Method used

Quinoline metal complexes, especially 8-hydroxyquinoline aluminum, are used as interface modifiers to form an interface modification layer at the interface between the perovskite layer and the electron transport layer, optimize interface contact, reduce defects, and react with interface defects through specific chemical properties to form stable chemical bonds or complexes to enhance the binding force and stability of the interface.

Benefits of technology

Through the formation of the interface modification layer, the photoelectric conversion efficiency and stability of the perovskite battery are improved, interface defects and resistance barriers are reduced, and short-circuit current and filling factor are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119789664A_ABST
    Figure CN119789664A_ABST
Patent Text Reader

Abstract

The invention discloses an interface modifier, a perovskite cell and a method for preparing a perovskite cell, and relates to the technical field of perovskite cell preparation. The interface modifier comprises a quinoline metal complex, and the quinoline metal complex is an 8-hydroxyquinoline metal complex. The interface modifier is mainly used to prepare an interface modification layer of the perovskite cell, and the interface modification layer is arranged between the perovskite light absorption layer and the electron transport layer of the perovskite cell. The 8-hydroxyquinoline metal complex is 8-hydroxyquinoline aluminum. The present invention uses a quinoline metal complex with 8-hydroxyquinoline aluminum as a main component as an interface modifier to form an interface modification layer at the buried interface of the perovskite layer and the electron transport layer, passivate the defects of the buried interface, thereby improving the photoelectric conversion efficiency and stability of the perovskite cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite battery preparation, and in particular to an interface modifier, a perovskite battery and a method for preparing the perovskite battery. Background Art

[0002] As a new generation of thin-film solar cells, perovskite solar cells have become the most promising emerging photovoltaic technology for commercial applications due to their high photoelectric conversion efficiency, low preparation cost and scalability. One of the main reasons that currently hinder the performance improvement of perovskite solar cells is that the growth direction of perovskite crystals toward the buried interface during the annealing process of perovskite thin films prepared by the solution method is difficult to control, which inevitably produces a large number of defects at the buried interface of the perovskite crystal and the interface of the electron transport layer. These defects will capture charge carriers, leading to non-radiative recombination, resulting in a significant reduction in the efficiency and stability of the photoelectric conversion device.

[0003] Therefore, it is necessary to develop a perovskite solar cell and modify the interface between the perovskite layer and the electron transport layer in the perovskite solar cell to reduce defects, thereby improving the photoelectric conversion efficiency and stability of the perovskite solar cell device. Summary of the invention

[0004] The main purpose of the present invention is to propose an interface modifier, a perovskite cell and a method for preparing a perovskite cell, aiming to modify the interface between the perovskite layer and the electron transport layer in the perovskite solar cell through the interface modification layer formed by the interface modifier, optimize the interface contact between the electron transport layer and the perovskite layer, reduce interface defects, passivate defects and enhance the bonding strength and stability of the interface.

[0005] To achieve the above object, the present invention provides an interface modifier, which includes a quinoline metal complex; the quinoline metal complex is an 8-hydroxyquinoline metal complex.

[0006] In one embodiment, the 8-hydroxyquinoline metal complex includes any one of 8-hydroxyquinoline aluminum and its derivatives, 8-hydroxyquinoline lithium and its derivatives, 8-hydroxyquinoline cesium and its derivatives, 8-hydroxyquinoline silver and its derivatives, 8-hydroxyquinoline-copper and its derivatives, 8-hydroxyquinoline-magnesium and its derivatives.

[0007] In one embodiment, the 8-hydroxyquinoline metal complex comprises 8-hydroxyquinoline aluminum.

[0008] The present invention also proposes a perovskite battery, which includes a stacked perovskite light-absorbing layer and an electron transport layer, an interface modification layer is provided between the perovskite light-absorbing layer and the electron transport layer, and the interface modification layer includes the interface modifier.

[0009] In one embodiment, the perovskite light absorbing layer includes a halide, and the halide includes at least one of CsI, CsBr, CsCl, KI, KBr, KCl, RbI, RbBr, RbCl, MAI, MABr, MACl, FAI, FABr, FACl, PbI2, PbBr2, and PbCl2.

[0010] In one embodiment, the electron transport layer includes a metal oxide, and the metal oxide includes at least one of SnO2, TiO2, ZnO, BaSnO3, and CeO2; or, the electron transport layer includes PCBM, C 60 At least one of.

[0011] In one embodiment, the perovskite cell includes a transparent conductive glass layer, the electron transport layer, the interface modification layer, the perovskite light absorption layer, a hole transport layer and a back electrode which are stacked in sequence.

[0012] In one embodiment, the perovskite cell includes a transparent conductive glass layer, a hole transport layer, the perovskite light absorbing layer, the interface modification layer, the electron transport layer and a back electrode which are stacked in sequence.

[0013] The present invention also proposes a method for preparing the perovskite battery, comprising the following steps:

[0014] The interface modifier is dissolved in a solvent to obtain an interface modifier solution, and the interface modifier solution is subjected to deposition and annealing treatment to obtain the interface modification layer.

[0015] In one embodiment, in the interface modifier solution, the concentration of the interface modifier is 0.1-3 mg / mL.

[0016] In one embodiment, the method for preparing the interface modification layer specifically comprises the following steps:

[0017] The interface modifier is dissolved in a solvent to obtain an interface modifier solution, and the interface modifier solution is deposited on the surface of the perovskite light-absorbing layer by spin coating, the spin coating speed is controlled to be 2500-3500 rpm, and the spin coating time is controlled to be 20-40s; then annealing is performed at 100°C-150°C for 10min-30min to obtain the interface modification layer.

[0018] In one embodiment, the method for preparing the interface modification layer specifically comprises the following steps:

[0019] The interface modifier is dissolved in a solvent to obtain an interface modifier solution, and the interface modifier solution is deposited on the surface of the electron transport layer by spin coating, the spin coating speed is controlled to be 2500-3500 rpm, and the spin coating time is controlled to be 20-40s; then annealing is performed at 100°C-150°C for 10min-30min to obtain the interface modification layer.

[0020] In one embodiment, the electron transport layer is prepared by depositing and annealing an electron transport layer precursor solution; the electron transport layer precursor solution includes the metal oxide, and the mass fraction of the metal oxide is 3 to 15 wt %; or, the electron transport layer precursor solution includes PCBM or C 60 , the PCBM or C 60 The concentration is 5mg / mL~25mg / mL.

[0021] In one embodiment, the perovskite light absorbing layer is prepared by depositing and annealing a perovskite precursor solution; the perovskite precursor solution includes the halide, and the concentration of the halide is 1 to 1.5M.

[0022] The technical solution of the present invention forms an interface modification layer at the buried interface of the perovskite layer and the electron transport layer by selecting a quinoline metal complex, especially 8-hydroxyquinoline aluminum, as an interface modifier; on the one hand, the interface contact between the electron transport layer and the perovskite layer can be optimized, the interface defects and the interface resistance barrier can be reduced, and the electron transport efficiency at the interface can be improved, thereby improving the short-circuit current and the filling factor of the perovskite battery, thereby improving the photoelectric conversion efficiency of the perovskite battery; on the other hand, 8-hydroxyquinoline aluminum has good film-forming properties and good thermal stability and chemical stability, and can form a dense film, which helps to protect the perovskite layer from the adverse effects of the external environment such as oxygen, moisture, ultraviolet light, etc. The quinoline ligand in 8-hydroxyquinoline aluminum can react with the defects of the buried interface through its specific chemical properties to form a stable chemical bond or complex, thereby enhancing the binding force and stability of the buried interface, thereby improving the stability of the perovskite battery; in addition, the present invention also obtains the appropriate concentration range of the quinoline ligand by exploring the photoelectric conversion performance of the perovskite battery prepared by the quinoline metal complex used to prepare the interface modification layer at different quinoline ligand concentrations. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0024] Figure 1 The photoelectric test curve diagram of the short-circuit current of the perovskite cells prepared in Examples 1-6 and Comparative Example 1 of the present invention;

[0025] Figure 2 A schematic structural diagram of a perovskite battery (formal structure) according to an embodiment of the present invention;

[0026] Figure 3 Schematic diagram of the structure of a perovskite battery (transformed structure) according to an embodiment of the present invention;

[0027] Description of Figure Numbers:

[0028] 1. Transparent conductive glass layer; 2. Electron transport layer; 3. Interface modification layer; 4. Perovskite light absorption layer; 5. Passivation layer; 6. Hole transport layer; 7. Metal back electrode.

[0029] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.

[0032] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features limited to "first" and "second" may explicitly or implicitly include at least one of the features. In addition, if "and / or" or "and / or" appears in the full text, its meaning includes three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or solutions that satisfy both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0033] The technical problem solved by the present application is: At present, in perovskite cells prepared by a solution method, it is difficult to control the growth direction of the perovskite crystals toward the buried interface during the annealing process, which inevitably produces a large number of defects at the interface between the buried interface of the perovskite crystal and the electron transport layer. These defects capture charge carriers, leading to non-radiative recombination, and significantly reducing the efficiency and stability of the photoelectric conversion device.

[0034] In order to solve the above technical problems and improve the photoelectric conversion efficiency and stability of perovskite cells prepared by a solution method, the present invention provides an interface modifier, a perovskite cell and a method for preparing a perovskite cell.

[0035] The invention provides an interface modifier, which comprises a quinoline metal complex; the quinoline metal complex is an 8-hydroxyquinoline metal complex.

[0036] It should be noted that the organic quinoline ligands in the quinoline metal complexes have excellent defect passivation ability. On the one hand, the organic quinoline ligands have multiple recognition sites, and the central metal ion, meso-position, β-position, etc. can all serve as molecular recognition sites. This structural diversity provides a broad space for optimizing the interface; on the other hand, the quinoline metal complexes can form coordination bonds or ionic bonds with the ions or atoms in the defects of the perovskite light absorption layer, thereby inhibiting non-radiative recombination. The advantages of hydroxyquinoline ligands over other quinoline ligands include good electron transfer ability and thermal stability, which are particularly important for the heat resistance of optoelectronic instruments and facilities, and the electron transfer ability of solar cells also determines their photoelectric conversion efficiency to a certain extent; therefore, hydroxyquinoline ligands are suitable for buried interface modification applications.

[0037] In one embodiment, the 8-hydroxyquinoline metal complex includes any one of 8-hydroxyquinoline aluminum and its derivatives, 8-hydroxyquinoline lithium and its derivatives, 8-hydroxyquinoline cesium and its derivatives, 8-hydroxyquinoline silver and its derivatives, 8-hydroxyquinoline-copper and its derivatives, 8-hydroxyquinoline-magnesium and its derivatives.

[0038] It should be noted that quinoline metal complexes also include derivatives of the above-mentioned complexes, such as derivatives of 8-hydroxyquinoline aluminum. The electronic transitions of these complexes mainly occur in π→π* transitions between different ligands, and in particular, the difluorosubstituted products of these complexes have the advantages of improved electron injection and charge transfer. In addition, the recently developed 8-hydroxyquinoline Schiff base derivatives and their aluminum and zinc complexes also have the above-mentioned characteristics and are suitable for improving interfacial electron transfer. The new double 8-hydroxyquinoline ligands and their zinc and aluminum coordination polymers also have advantages in electron transfer performance and thermal stability, and are also suitable for improving interfacial electron transfer.

[0039] In one embodiment, the 8-hydroxyquinoline metal complex comprises 8-hydroxyquinoline aluminum.

[0040] It should be noted that the metal ions in the quinoline metal complex have a high electron mobility, which has a positive effect on the current efficiency in the buried interface. The electron mobility of aluminum in 8-hydroxyquinoline aluminum is 10 -3 ~10 -4 cm 2 ·V -1 ·s -1 The order of magnitude has a great contribution to the improvement of the electron mobility in the interface layer, and also plays an important role in improving the overall efficiency of perovskite solar cells.

[0041] It should also be noted that there are three quinoline units in the 8-hydroxyquinoline aluminum molecule, each of which can act as an independent ligand to bind to metal ions. It can also act as a tridentate ligand to bind to a central metal ion such as Sn in SnO2. 4+ or Pb in perovskite 2+ ) forms a stable coordination compound, and the multidentate ligand property strengthens the binding force between the molecule and the defect site, improving the stability and durability of the passivation. The 8-hydroxyquinoline aluminum molecule has a large π-conjugated system, which helps to enhance the planarity and rigidity of the molecule, making it easier to form an orderly arrangement on the surface, thereby effectively covering and passivating surface defects.

[0042] The present invention also proposes a perovskite battery, which includes a stacked perovskite light-absorbing layer and an electron transport layer, an interface modification layer is provided between the perovskite light-absorbing layer and the electron transport layer, and the interface modification layer includes the interface modifier.

[0043] It should be noted that the interface of the annealed perovskite light-absorbing layer obtained under normal circumstances is uneven, so there are defects in the buried interface at the perovskite light-absorbing layer and the electron transport layer, which will cause non-radiative recombination. The present invention provides an interface modification layer between the electron transport layer and the perovskite light-absorbing layer, and the interface modification layer is prepared by a quinoline metal complex. The organic quinoline ligand in the quinoline metal complex has excellent defect passivation ability. On the one hand, the organic quinoline ligand has multiple recognition sites, and the central metal ion, meso-position, β-position, etc. can all be used as molecular recognition sites. The diversity of this structure provides a broad space for optimizing the interface; on the other hand, the quinoline metal complex can form a coordination bond or an ionic bond with the ions or atoms in the defects of the perovskite light-absorbing layer, thereby inhibiting non-radiative recombination. Some quinoline metal complexes have high hydrophobicity, and introducing them into the surface of the perovskite can form a mixed-dimensional perovskite, which prevents the invasion of moisture in the air, thereby improving the stability of the perovskite to humidity.

[0044] It should also be noted that the interface modification layer is prepared by attaching a quinoline metal complex solution to a perovskite light-absorbing layer or an electron transport layer. The inventors obtained this through multiple experiments during the research and development process for conventional perovskite cells (both formal and trans structures).

[0045] In one embodiment, the perovskite light absorbing layer includes a halide, and the halide includes at least one of CsI, CsBr, CsCl, KI, KBr, KCl, RbI, RbBr, RbCl, MAI, MABr, MACl, FAI, FABr, FACl, PbI2, PbBr2, and PbCl2.

[0046] It should be noted that the perovskite precursor solution in the perovskite light absorbing layer of the present invention is prepared by dissolving one or more of CsI, FAI, MABr, MACl, PbI2 and PbBr2 in a mixed solvent, wherein it can be CsI, FAI, FAI, MABr, PbI2, or MACl, PbI2 and PbBr2, including but not limited to the combination of the above substances. It should also be noted that the molecular formula of the perovskite precursor solution is (FA x MA 1-x )yC 1-y Pb(I z Br 1-z )3, where 0≤x≤1, 0≤y≤1, 0≤z≤1.

[0047] In one embodiment, the electron transport layer includes a metal oxide, and the metal oxide includes at least one of SnO2, TiO2, ZnO, BaSnO3, and CeO2.

[0048] It should be noted that the interface modification layer prepared by the interface modifier in the present invention can have a good passivation effect on the interface between the perovskite light absorbing layer and the electron transport layer prepared by the above-mentioned substances, can effectively reduce the interface energy barrier between the two, and promote the transmission of carriers between the electron transport layer and the perovskite layer.

[0049] It should be noted that perovskite cells include formal structures and trans structures. When quinoline metal complexes are used as interface modification layers, they can play a role in both the formal structure and the trans structure.

[0050] Specifically, refer to Figure 2 In one embodiment (formal structure), the perovskite cell includes a transparent conductive glass 1, an electron transport layer 2, an interface modification layer 3, a perovskite light absorption layer 4, a hole transport layer 6 and a metal back electrode 7 which are stacked in sequence.

[0051] Specifically, refer to Figure 3In one embodiment (transverse structure), the perovskite cell includes a transparent conductive glass layer 1, a hole transport layer 6, a perovskite light absorption layer 4, an interface modification layer 3, an electron transport layer 2 and a metal back electrode 7 which are stacked in sequence.

[0052] In one embodiment, the transparent conductive glass layer 1 is made of transparent conductive glass after cleaning, including FTO conductive glass, ITO conductive glass or other transparent conductive glass, wherein FTO is represented by fluorine-doped SnO2 conductive glass (SnO2:F), and ITO is represented by indium-doped SnO2 conductive glass (SnO2:In). It should be noted that the present application does not limit the general category of conductive glass.

[0053] In one embodiment, the electron transport layer 2 includes a TiO2 electron transport layer, a SnO2 electron transport layer, a ZnO electron transport layer, a BaSnO3 electron transport layer or a CeO2 electron transport layer. The above materials are more suitable for the formal structure, and the electron transport layer materials of the trans structure are more suitable for PCBM and C 60 , where PCBM is a fullerene derivative, C 60 It should be noted that the present application does not limit the general category of electron transport layer materials.

[0054] In one embodiment, the hole transport layer 6 includes a P3HT hole transport layer, a Spiro-OMeTAD hole transport layer, a NiO hole transport layer, a PEDOT:PSS hole transport layer, a SAM hole transport layer or a PTAA hole transport layer; it should be noted that because the materials of the hole transport layer suitable for the formal structure and the trans structure are different, the hole transport layer material of the formal structure is more suitable for Spiro-OMeTAD, and the hole transport layer material of the trans structure is more suitable for P3HT, NiO, PEDOT:PSS, SAM and PTAA. Wherein, P3HT represents poly 3-hexylthiophene, Spiro-OMeTAD represents 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, NiO represents nickel oxide, PEDOT:PSS represents poly 3,4-ethylenedioxythiophene / polystyrene sulfonate, SAM represents self-assembled small molecules, and PTAA represents poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]. It should be noted that the present application does not limit the total type of hole transport layer materials.

[0055] In one embodiment, the material of the metal back electrode 7 includes gold, silver, copper, aluminum, carbon and metal oxide, etc., and also includes a mixture of two or more of the above. It should be noted that the present application does not limit the general type of metal back electrode materials.

[0056] The present invention also provides a method for preparing the perovskite battery. In the perovskite battery, the method for preparing the interface modification layer comprises the following steps:

[0057] The interface modifier is dissolved in a solvent to obtain an interface modifier solution, and the interface modifier solution is subjected to deposition and annealing treatment to obtain the interface modification layer.

[0058] In one embodiment, in the interface modifier solution, the concentration of the interface modifier is 0.1 to 3 mg / mL. Optionally, in the interface modifier solution, the concentration of the interface modifier is 0.5 to 2 mg / mL. It should be noted that the interface modification layer is prepared by attaching a quinoline metal complex solution to a perovskite light-absorbing layer or an electron transport layer, so it is necessary to control the content of quinoline ligands in the quinoline metal complex solution; when there is only one interface modifier, 8-hydroxyquinoline aluminum, in the interface modifier solution and the concentration of 8-hydroxyquinoline aluminum is 0.5 to 2 mg / mL, the obtained perovskite battery has a higher battery conversion efficiency.

[0059] In one embodiment, the method for preparing the interface modification layer specifically comprises the following steps:

[0060] The interface modifier is dissolved in a solvent to obtain an interface modifier solution, and the interface modifier solution is deposited on the surface of the perovskite light-absorbing layer by spin coating, the spin coating speed is controlled to be 2500-3500 rpm, and the spin coating time is controlled to be 20-40s; then annealing is performed at 100°C-150°C for 10min-30min to obtain the interface modification layer.

[0061] In one embodiment, the method for preparing the interface modification layer specifically comprises the following steps:

[0062] The interface modifier is dissolved in a solvent to obtain an interface modifier solution, and the interface modifier solution is deposited on the surface of the electron transport layer by spin coating, the spin coating speed is controlled to be 2500-3500 rpm, and the spin coating time is controlled to be 20-40s; then annealing is performed at 100°C-150°C for 10min-30min to obtain the interface modification layer.

[0063] In one embodiment, the electron transport layer is prepared by depositing and annealing an electron transport layer precursor solution; the electron transport layer precursor solution includes the metal oxide, and the mass fraction of the metal oxide is 3 to 15 wt %.

[0064] In one embodiment, the electron transport layer precursor solution includes the PCBM or C 60 , the PCBM or C 60 The concentration is 5-25 mg / mL.

[0065] It should be noted that in the electron transport layer precursor solution, the mass fraction of the metal oxide can be any one of 3wt%, 3.1wt%, 3.4wt%, 8.5wt% and 15wt%; including but not limited to the above values, as long as the concentration value is within the range, under the conditions of the above concentration range, the interface modification layer can have a better interface passivation effect on the electron transport layer, the electron transport layer has fewer defects, and is conducive to electron transport.

[0066] In one embodiment, the perovskite light absorbing layer is prepared by deposition and annealing of a perovskite precursor solution; the perovskite precursor solution includes the halide, and the concentration of the halide is 1 to 1.5 M. It should be noted that in the perovskite precursor solution, the concentration of the halide can be any one of 1M, 1.1M, 1.3M, and 1.5M; including but not limited to the above values, as long as the concentration value is within the range, under the conditions of the above concentration range, the interface modification layer has a better interface passivation effect on the perovskite light absorbing layer, can make the interface defects of the perovskite light absorbing layer less, and can also make the interface energy barrier between the electron transport layer and the perovskite layer closer, which is more conducive to electron transport.

[0067] Specifically, the preparation method of the above-mentioned perovskite battery (formal structure) includes the following steps:

[0068] S1a, using glass cleaning agent, deionized water, ethanol and isopropanol in sequence to ultrasonically clean the TCO conductive glass for 10 minutes, blowing the TCO conductive glass dry, and performing ultraviolet ozone cleaning (UVO) treatment for 15 minutes to 30 minutes to obtain a transparent conductive glass layer 1.

[0069] Optionally, the cleaning agent is not limited to the glass cleaning agent, deionized water, ethanol and isopropyl alcohol listed above.

[0070] S2a, depositing a SnO2 aqueous solution with a concentration of 3wt%-15wt% on one surface of the transparent conductive glass layer, and annealing at 100°C-150°C for 10-30min to obtain an electron transport layer 2.

[0071] Optionally, the material of the electron transport layer 2 is not limited to SnO 2 , and the present invention does not limit the general type of the material of the electron transport layer 2 .

[0072] S3a, depositing an 8-hydroxyquinoline aluminum solution with a concentration of 0.1 mg / mL to 3 mg / mL on the electron transport layer 2 by spin coating or immersion, and annealing at 100° C. to 150° C. for 10 min to 30 min to obtain an interface modification layer 3.

[0073] Optionally, the material of the interface modification layer 3 is not limited to 8-hydroxyquinoline aluminum.

[0074] S4a, CsI, FAI, MABr, MACl, PbI2 and PbBr2 were dissolved in a mixed solution of DMF and DMSO with a volume ratio of 8:2 at a certain molar ratio to prepare a 1.0M-1.5M (FA x MA 1-x )yC 1-y Pb(I z Br 1-z )3 solution, and then stir for 6h~12h to obtain a perovskite precursor solution. The surface of the interface modification layer of the sample prepared in step S3a is first spin-coated with the perovskite precursor solution at a low speed of 500rpm~2500rpm in an inert atmosphere glove box for 5~10s, and then spin-coated with the perovskite precursor solution at a high speed of 4000rpm~5000rpm for 20~40s. Anti-solvent is added dropwise 5~10s before the end of spin coating, and then annealed at 100°C for 5~60 minutes to obtain the perovskite light absorbing layer 4.

[0075] Optionally, the anti-solvent is selected from one or more of chlorobenzene, ether or ethyl acetate; specifically, the preparation method of the perovskite light absorbing layer may also adopt a slit coating method or a spray coating method in addition to the spin coating method.

[0076] Optionally, the inert atmosphere includes at least one of nitrogen, helium, neon, argon, krypton, xenon and radon.

[0077] S5a, spin coating a 0.3 mg / mL to 5 mg / mL n-octylammonium iodide (OAI) solution on the surface of the perovskite light absorbing layer 4 at a rotation speed of 5000 rpm for 10 s to 60 s, followed by annealing at 100° C. for 5 min to 10 min to obtain a passivation layer 5.

[0078] Optionally, the material of the passivation layer 5 is not limited to n-octylammonium iodide. Optionally, the passivation layer 5 may be prepared by a slit coating method or a spray coating method in addition to the spin coating method.

[0079] S6a, spin-coating the Spiro-OMeTAD solution on the surface of the passivation layer 5 for 10s to 60s to obtain the hole transport layer 6.

[0080] Optionally, the present invention does not limit the concentration of the Spiro-OMeTAD solution. Optionally, the preparation method of the hole transport layer 6 may also be a slit coating method or a spray coating method in addition to the spin coating method.

[0081] S7a, depositing a metal back electrode 7 on the surface of the hole transport layer 6 to obtain a perovskite cell (formal structure).

[0082] Optionally, the present invention does not limit the thickness of the metal back electrode; optionally, the thickness of the metal back electrode is 80nm to 120nm; optionally, the present invention does not limit the material of the metal back electrode; optionally, the material of the metal back electrode is selected from one of Cu, Ag, Al, and Au.

[0083] The present invention also proposes a method for preparing a perovskite battery, comprising the following steps:

[0084] A hole transport layer 6, a perovskite light absorption layer 4, an interface modification layer 3, an electron transport layer 2 and a metal back electrode 7 are sequentially prepared on a transparent conductive glass layer 1 to prepare the perovskite cell;

[0085] Wherein, the interface modification layer 3 is prepared from a quinoline metal complex solution.

[0086] In one embodiment, the preparation process of the interface modification layer 3 includes the following steps:

[0087] The quinoline metal complex solution is attached to the surface of the electron transport layer 2 by spin coating or immersion, and annealed at 100° C. to 150° C. for 10 min to 30 min to obtain the interface modification layer 3. It should be noted that maintaining the same annealing temperature for the electron transport layer 2, the interface modification layer 3 and the perovskite light absorption layer 4 is beneficial to enhancing the mutual bonding force, and is also beneficial to maintaining the same crystal growth rate so that the interface of the perovskite crystal or other crystal after crystallization is smoother.

[0088] Specifically, the preparation method of the above-mentioned perovskite battery (transformed structure) comprises the following steps:

[0089] S1b, using glass cleaning agent, deionized water, ethanol and isopropanol in sequence to ultrasonically clean the TCO conductive glass for 10 minutes, blowing the TCO conductive glass dry, and performing ultraviolet ozone cleaning (UVO) treatment for 15 minutes to 30 minutes to obtain a transparent conductive glass layer 1.

[0090] Optionally, the cleaning agent is not limited to the glass cleaning agent, deionized water, ethanol and isopropyl alcohol listed above.

[0091] S2b, spin coating the SAM solution on the surface of the transparent conductive glass layer for 10s to 60s to obtain a hole transport layer 6.

[0092] Optionally, the present invention does not limit the concentration of the SAM solution. Optionally, the preparation method of the hole transport layer 6 may also be a slit coating method or a spray coating method in addition to the spin coating method.

[0093] S3b, spin coating a 0.3 mg / mL to 5 mg / mL n-octylammonium iodide (OAI) solution on the surface of the hole transport layer 6 at a rotation speed of 5000 rpm for 10 s to 60 s, followed by annealing at 100° C. for 5 min to 10 min to obtain a passivation layer 5.

[0094] Optionally, the material of the passivation layer 5 is not limited to n-octylammonium iodide. Optionally, the passivation layer 5 may be prepared by a slit coating method or a spray coating method in addition to the spin coating method.

[0095] S4b, CsI, FAI, MABr, MACl, PbI2 and PbBr2 are dissolved in a mixed solution of DMF and DMSO with a volume ratio of 8:2 in a certain molar ratio to prepare a 1.0M-1.5M (FAxMA1-x)yCs1-yPb(IzBr1-z)3 solution, and then stirred for 6h~12h to obtain a perovskite precursor solution. The surface of the passivation layer 5 of the sample prepared in step S3b is first spin-coated with the perovskite precursor solution at a low speed of 500rpm~2500rpm in an inert atmosphere glove box for 5~10s, and then spin-coated with the perovskite precursor solution at a high speed of 4000rpm~5000rpm for 20~40s. An anti-solvent is added dropwise 5~10s before the end of spin coating, and then annealed at 100°C for 5~60 minutes to obtain a perovskite light absorbing layer 4.

[0096] Optionally, the anti-solvent is selected from one or more of chlorobenzene, ether or ethyl acetate; specifically, the preparation method of the perovskite light absorbing layer 4 may also adopt a slit coating method or a spray coating method in addition to the spin coating method.

[0097] Optionally, the inert atmosphere includes at least one of nitrogen, helium, neon, argon, krypton, xenon and radon.

[0098] S5b, depositing a 0.1 mg / mL to 3 mg / mL 8-hydroxyquinoline aluminum solution on the perovskite light absorbing layer 4 by spin coating or immersion, and annealing at 100° C. to 150° C. for 10 min to 30 min to obtain an interface modification layer 3.

[0099] S6b, depositing a PCBM solution with a concentration of 5 mg / mL to 25 mg / mL on the surface of the interface modification layer 3, annealing at 100°C-150°C for 10-30 min, to obtain the electron transport layer 2.

[0100] Optionally, the material of the electron transport layer is not limited to PCBM, and the present invention does not limit the general type of the material of the electron transport layer 2 .

[0101] S7b, depositing a metal back electrode on the surface of the electron transport layer 2 to obtain a perovskite cell (transform structure).

[0102] Optionally, the present invention does not limit the thickness of the metal back electrode 7; optionally, the thickness of the metal back electrode 7 is 80nm to 120nm; optionally, the present invention does not limit the material of the metal back electrode 7; optionally, the material of the metal back electrode 7 is selected from one of Cu, Ag, Al, and Au.

[0103] The present invention also proposes a perovskite battery assembly, including the above-mentioned perovskite battery (formal structure), or, including the above-mentioned perovskite battery (trans structure).

[0104] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0105] Example 1

[0106] The preparation process of the perovskite battery in Example 1 includes the following steps:

[0107] (1) using a glass cleaning agent, deionized water, ethanol and isopropanol in sequence to ultrasonically clean the TCO conductive glass for 10 minutes, blowing the FTO conductive glass dry with a nitrogen stream, and performing an ultraviolet ozone cleaning (UVO) treatment for 15 minutes to obtain a transparent conductive glass layer 1;

[0108] (2) A 15 wt % SnO2 hydrocolloid solution and deionized water were mixed in a volume ratio of 2:1 to obtain a mixed solution, and 100 μL of the mixed solution was deposited on the transparent conductive glass layer 1 by spin coating at a spin coating speed of 3000 rpm for 30 s, followed by annealing at 150° C. for 10 min to obtain an electron transport layer 2;

[0109] (3) depositing an ethanol solution of 8-hydroxyquinoline aluminum with a concentration of 1 mg / mL on the electron transport layer by spin coating, with the amount of the spin coating solution being 100 μL, the spin coating speed being 3000 rpm, the spin coating time being 30 s, and annealing at 120° C. for 10 min to obtain an interface modification layer 3;

[0110] (4) Dissolve 19.5 mg of CsI, 244.7 mg of FAI and 691.5 mg of PbI2 in 1 mL of a mixed solution of DMF and DMSO in a volume ratio of 8:2, and stir for 10 h to obtain a perovskite precursor solution; first spin-coat the surface of the interface modification layer of the sample prepared in step (3) with the perovskite precursor solution at a low speed of 2000 rpm in an inert atmosphere glove box for 10 s, and then spin-coat the perovskite precursor solution at a high speed of 4000 rpm to 5000 rpm for 40 s. The total amount of the perovskite precursor solution spin-coated is 100 μL. 200 μL of anti-solvent chlorobenzene is added dropwise 10 s before the end of the spin coating, and then annealed at 100° C. for 20 minutes to obtain a perovskite light absorbing layer 4;

[0111] (5) Spin coating a 2 mg / mL octyl ammonium iodide (OAI) solution on the surface of the perovskite light absorbing layer 4 at a rotation speed of 5000 rpm, the amount of the spin coating solution is 100 μL, the spin coating time is 30 s, and then annealing at 100° C. for 5 min to obtain a passivation layer 5;

[0112] (6) 72.5 mg of Spiro-OMeTAD, 1 mL of chlorobenzene, 28.5 μL of 4-tert-butylpyridine and 18 μL of lithium bis(trifluoromethanesulfonyl)imide acetonitrile solution (concentration of 520 mg / mL) were mixed and stirred for 12 h to prepare a Spiro-OMeTAD solution, which was deposited on the passivation layer 5 by spin coating. The amount of the spin coating solution was 100 μL, the spin coating speed was 4000 rpm, and the spin coating time was 30 s to prepare a hole transport layer 6;

[0113] (7) A 100 nm thick back electrode Ag is prepared on the hole transport layer 6 by vacuum thermal evaporation to obtain a perovskite cell.

[0114] Example 2

[0115] Example 2 is based on Example 1, except that the concentration of 8-hydroxyquinoline aluminum in Example 2 is 0.1 mg / mL.

[0116] Example 3

[0117] Example 3 is based on Example 1, except that the concentration of 8-hydroxyquinoline aluminum in Example 3 is 0.5 mg / mL.

[0118] Example 4

[0119] Example 4 is based on Example 1, except that the concentration of 8-hydroxyquinoline aluminum in Example 4 is 1.5 mg / mL.

[0120] Example 5

[0121] Example 5 is based on Example 1, except that the concentration of 8-hydroxyquinoline aluminum in Example 5 is 2 mg / mL.

[0122] Example 6

[0123] Example 6 is based on Example 1, except that the concentration of 8-hydroxyquinoline aluminum in Example 6 is 3 mg / mL.

[0124] Comparative Example 1

[0125] Comparative Example 1 is based on Example 1, except that: the perovskite battery structure in Comparative Example 1 does not include an interface modification layer, that is, the preparation method of the perovskite battery in Comparative Example 1 includes the following steps:

[0126] (1) using a glass cleaning agent, deionized water, ethanol and isopropanol in sequence to ultrasonically clean the TCO conductive glass for 10 minutes, blowing the FTO conductive glass dry with a nitrogen stream, and performing an ultraviolet ozone cleaning (UVO) treatment for 15 minutes to obtain a transparent conductive glass layer 1;

[0127] (2) A 15 wt % SnO2 hydrocolloid solution and deionized water were mixed in a volume ratio of 2:1 to obtain a mixed solution, and 100 μL of the mixed solution was deposited on the transparent conductive glass layer 1 by spin coating at a spin coating speed of 3000 rpm for 30 s, followed by annealing at 150° C. for 10 min to obtain an electron transport layer 2;

[0128] (3) Dissolve 19.5 mg of CsI, 244.7 mg of FAI and 691.5 mg of PbI2 in 1 mL of a mixed solution of DMF and DMSO in a volume ratio of 8:2, and stir for 10 h to obtain a perovskite precursor solution; first spin-coat the surface of the electron transport layer 2 of the sample prepared in step (3) with the perovskite precursor solution at a low speed of 2000 rpm in an inert atmosphere glove box for 10 s, and then spin-coat the perovskite precursor solution at a high speed of 4000 rpm to 5000 rpm for 40 s. The total amount of the perovskite precursor solution spin-coated is 100 μL. 200 μL of anti-solvent chlorobenzene is added dropwise 10 s before the end of the spin coating, and then annealed at 100° C. for 20 minutes to obtain a perovskite light absorbing layer 4;

[0129] (4) Spin coating a 2 mg / mL octyl ammonium iodide (OAI) solution on the surface of the perovskite light absorbing layer 4 at a rotation speed of 5000 rpm, the amount of the spin coating solution is 100 μL, the spin coating time is 30 s, and then annealing at 100° C. for 5 min to obtain a passivation layer 5;

[0130] (5) 72.5 mg of Spiro-OMeTAD, 1 mL of chlorobenzene, 28.5 μL of 4-tert-butylpyridine and 18 μL of lithium bis(trifluoromethanesulfonyl)imide acetonitrile solution (concentration of 520 mg / mL) were mixed and stirred for 12 h to prepare a Spiro-OMeTAD solution, which was deposited on the passivation layer 5 by spin coating. The amount of the spin coating solution was 100 μL, the spin coating speed was 4000 rpm, and the spin coating time was 30 s to prepare a hole transport layer 6;

[0131] (6) A metal back electrode Ag with a thickness of 100 nm was prepared on the hole transport layer 6 by vacuum thermal evaporation to obtain a perovskite cell.

[0132] Performance Testing

[0133] The short-circuit current (mAcm-2), open-circuit voltage (V), photoelectric conversion efficiency (%) and fill factor of the perovskite cells prepared in Examples 1-6 and Comparative Example 1 were measured respectively, and the measurement results are shown in Table 1. At the same time, the inventors also measured the photoelectric test curve of the short-circuit current of the perovskite cells prepared in Examples 1-6 and Comparative Example 1, as shown in Table 1. Figure 1 ; Figure 1 The different concentrations in the middle curve refer to the concentration of 8-hydroxyquinoline aluminum, and the “control” group corresponds to the group corresponding to the comparative example.

[0134] Table 1

[0135] Test items <![CDATA[Short-circuit current (mAcm -2 )]]> Open circuit voltage(V) Photoelectric conversion efficiency (%) Fill factor (%) Example 1 26.55 1.131 25.84 86.07 Example 2 25.80 1.079 23.01 82.69 Example 3 26.02 1.101 23.86 83.27 Example 4 26.41 1.121 25.09 84.79 Example 5 26.09 1.117 24.31 83.42 Example 6 26.04 1.115 23.99 82.59 Comparative Example 1 25.71 1.072 22.59 81.96

[0136] By comparing Table 1 and Figure 1 The data were analyzed and it was found that the performance parameters such as short-circuit current, open-circuit voltage, photoelectric conversion efficiency and fill factor of the perovskite cells in Examples 1-6 were significantly higher than those in Comparative Example 1. It can be seen that the use of 8-hydroxyquinoline aluminum to form an interface modification layer between the electron transport layer and the perovskite light absorbing layer of the perovskite cell is significantly beneficial to the improvement of the photoelectric performance; the performance parameters in Example 1 and Example 4 are significantly better than those in other examples. It can be seen that when the concentration of the 8-hydroxyquinoline aluminum solution is 1 to 1.5 mg / mL, the photoelectric performance of the perovskite cell is best improved.

[0137] The above description is only an exemplary embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. An interfacial modifier, characterized in that: The interface modifier includes a quinoline metal complex; the quinoline metal complex is an 8-hydroxyquinoline metal complex.

2. The interfacial modifier according to claim 1, characterized in that The 8-hydroxyquinoline metal complex includes any one of 8-hydroxyquinoline aluminum and its derivatives, 8-hydroxyquinoline lithium and its derivatives, 8-hydroxyquinoline cesium and its derivatives, 8-hydroxyquinoline silver and its derivatives, 8-hydroxyquinoline-copper and its derivatives, 8-hydroxyquinoline-magnesium and its derivatives.

3. The interface modifier according to claim 1, characterized in that The 8-hydroxyquinoline metal complex includes 8-hydroxyquinoline aluminum.

4. A perovskite battery, characterized in that: The perovskite cell comprises a stacked perovskite light-absorbing layer and an electron transport layer, an interface modification layer is further provided between the perovskite light-absorbing layer and the electron transport layer, and the interface modification layer comprises the interface modifier according to any one of claims 1 to 3.

5. The perovskite battery according to claim 4, characterized in that: The electron transport layer includes a metal oxide, and the metal oxide includes at least one of SnO2, TiO2, ZnO, BaSnO3, and CeO2; or the electron transport layer includes PCBM, C 60 at least one of; And / or, the perovskite light-absorbing layer includes a halide, and the halide includes at least one of CsI, CsBr, CsCl, KI, KBr, KCl, RbI, RbBr, RbCl, MAI, MABr, MACl, FAI, FABr, FACl, PbI2, PbBr2, and PbCl2.

6. The perovskite battery according to claim 4, characterized in that: The perovskite cell comprises a transparent conductive glass layer, an electron transport layer, an interface modification layer, a perovskite light absorption layer, a hole transport layer and a back electrode which are stacked in sequence; Alternatively, the perovskite cell comprises a transparent conductive glass layer, a hole transport layer, the perovskite light absorbing layer, the interface modification layer, the electron transport layer and a back electrode which are stacked in sequence.

7. A method for preparing a perovskite battery according to any one of claims 4 to 6, characterized in that: In the perovskite battery, the method for preparing the interface modification layer comprises the following steps: The interface modifier is dissolved in a solvent to obtain an interface modifier solution, and the interface modifier solution is subjected to deposition and annealing treatment to obtain the interface modification layer.

8. The method for preparing a perovskite battery according to claim 7, characterized in that: In the interface modifier solution, the concentration of the interface modifier is 0.1-3 mg / mL.

9. The method for preparing a perovskite battery according to claim 7, characterized in that: The preparation method of the interface modification layer specifically comprises the following steps: The interface modifier is dissolved in a solvent to obtain an interface modifier solution, and the interface modifier solution is deposited on the surface of the perovskite light absorbing layer by spin coating, the spin coating speed is controlled to be 2500-3500 rpm, and the spin coating time is controlled to be 20-40 s; then annealing is performed at 100° C. to 150° C. for 10 min to 30 min to obtain the interface modification layer; Alternatively, the method for preparing the interface modification layer specifically comprises the following steps: The interface modifier is dissolved in a solvent to obtain an interface modifier solution, and the interface modifier solution is deposited on the surface of the electron transport layer by spin coating, the spin coating speed is controlled to be 2500-3500 rpm, and the spin coating time is controlled to be 20-40s; then annealing is performed at 100°C-150°C for 10min-30min to obtain the interface modification layer.

10. The method for preparing a perovskite battery according to claim 7, characterized in that: The electron transport layer is prepared by depositing and annealing an electron transport layer precursor solution; The electron transport layer precursor solution includes a metal oxide, and the mass fraction of the metal oxide is 3 to 15 wt %; or, the electron transport layer precursor solution includes PCBM or C 60 , the PCBM or C 60 The concentration is 5mg / mL~25mg / mL; And / or, the perovskite light-absorbing layer is prepared by depositing and annealing a perovskite precursor solution; the perovskite precursor solution includes a halide, and the concentration of the halide is 1 to 1.5M.